카본블랙 충진 PMC의 Percolation Threshold와 도전율 임계지수에 관한 연구 - 신순기; Soon Gi Shin (대한금속·재료학회지, 48(9), 2010)
In this paper, the percolation behavior, the critical exponent of conductivity, and the electrical conduction mechanism of polyethylene matrix composites are discussed based on studying the whole change of the resistivity and dielectric constant for carbon black loading. There are two transitions of resistivity for carbon black loading. Below the first transition, resistivity shows an ohmic behavior, and its value is almost the same as that of polyethylene. Between the first and second transitions, the change in resistivity is very sharp, leading to a large critical exponent of conductivity, and a non-ohmic electric field dependence of current has been observed. This electric field dependence has been discussed with a tunneling conduction. Beyond the second transition, the electric field dependence of current shows an ohmic behavior and a gentle change in resistivity has been observed for carbon black loading. The critical exponent of conductivity estimated by using the second transition is satisfied with the universal law of conductivity. The dielectric constant has been observed beyond the first transition and diverges around the second transition. It was concluded that the percolation threshold should be the second transition of resistivity for the polyethylene matrix composites loaded carbon black.